Die verhouding ouermentoraat, geloofsidentiteit en betrokkenheid van jongmense na belydenisaflegging (Afrikaans) - Avenant, Johannes Cornelius (2013)
This study flows from an awareness of the crisis in the church, and specifically in the Dutch Reformed Church The Reeds, concerning the lack of faith identity as well as the lack of assimilation with the faith community after confirmation. The hypothesis chosen for this study, which also determined the opening argument, was that parental mentorship and involvement of parents in faith development assist in the development, understanding and living of children’s faith identity as well as their assimilation with the faith community after confirmation. The opposite of this is also made clear – a lack of parental mentorship and involvement of parents in faith development is the cause of the absence of faith identity and assimilation with the faith community after confirmation. From a perspective of building up the local church this hypothesis is examined theologically, psychologically and empirically. The study concludes that this hypothesis definitely holds ground. The role of the involvement or absence of parents in children’s faith identity and faith development is examined. The role of the faith community in supporting parents with their mentoring role is also probed and the results clearly indicate the need for an adjustment in the approach of the church’s youth ministry. Another meaningful finding is that there has been a shift in the past few decades (regarding where the responsibility for the development of children’s faith lie) from parents to the faith community. Parents were gradually shifted out of youth ministry, which caused the drop-off culture that currently exists. To ensure a generation that understands and live their faith identity and who are still actively involved in their faith community after confirmation, begs for definite action. To address this crisis, different strategies and action plans are proposed in order to move away from church-centred, home-supporting youth ministry to home-centred, church-supporting youth ministry. This implies long-term implementation and will result in parents once again taking primary responsibility for the faith development of their children. This further infers that faith communities must include parents in the ministry to children before and during their Sunday-school and catechism years. Copyright === Dissertation (MA(Theol))--University of Pretoria, 2012. === Practical Theology === unrestricted